Учебное сотрудничество как средство повышения эффективности процесса обучения иностранному языку - Рахметова, А.А.; Бурмагина, Л.А. (My University, 2016)
The problem of group work is widely worked out recently. In comparison with individual work, group collaboration is more efficient in learning a foreign language. Successful foreign language learning depends on the coordination of actions of a teacher and students.
Keywords: educational cooperation; education system; resources of education foreign language; efficiency of educational process